Les restructurations de la formation supérieure en Grande-Bretagne : réponse aux besoins des employeurs ou régulation de l'accès à l'enseignement supérieur ? - Brenda Little; Yann Lebeau (Les éditions de la Maison des sciences de l'Homme, 2005)
In Great Britain, changes to the nature and shape of short-cycle, workrelated higher education are being introduced within the context of an expanding higher education system. As is often the case, government justifies these changes in terms of meeting the needs of the economy. At a time when the first cohort of graduates from the (newly-introduced) Foundation Degree (broadly equivalent to a Bac+2) is entering the labour market, the authors consider the place of such programmes, both in terms of new labour's agenda for widening participation to higher education, and from employers' own perceptions of these programmes. The article is based on a study undertaken by the authors (and others) in 2003 for the Learning and Skills Council. The study included interviews with British employers, and an analysis of recent policy documents relating to higher education - in particular, the introduction of more work-related programmes aimed at producing the skills required for associate professional and higher technician occupations.